Legalising the drug wars : a regulatory history of UN drug control - Collins, John, 1986- (Cambridge : Cambridge University Press, 2022)
Where did the regulatory underpinnings for the global drug wars come from? This book is the first fully-focused history of the 1961 UN Single Convention on Narcotic Drugs, the bedrock of the modern multilateral drug control system and the focal point of global drug regulations and prohibitions. Although far from the propagator of the drug wars, the UN enabled the creation of a uniform global legal framework to effectively legalise, or regulate, their pursuit. This book thereby answers the question of where the international legal framework for drug control came from, what state interests informed its development and how complex diplomatic negotiations resulted in the current regulatory system, binding states into an element of global policy uniformity.
Introduction -- Drug diplomacy from the opium wars through The League Of Nations, 1839-1939 -- International drug control in wartime , 1939-1945 -- Creating the UN Commission on Narcotic Drugs, 1945-1946 -- Reconstructing drug control in Europe, Asia and the Middle East -- Old battles a new at the UN Commission on Narcotic Drugs, 1946-1948 -- Dividing up the global licit market, 1948-1953 -- From the 1953 protocol to the 1961 single convention -- Assessing the legal legacy of the single convention -- Conclusion : UN drug control in the twenty-first century - towards a regime complex?
Title from publisher's bibliographic system (viewed on 25 Nov 2021).
Keywords: United Nations. -- Commission on Narcotic Drugs -- History -- 20th century; Single Convention on Narcotic Drugs -- (1961 March 30); Drugs of abuse -- Law and legislation -- Criminal provisions -- History -- 20th century; Drug control -- International cooperation -- History -- 20th century; Narcotic laws -- History -- 20th century